2017
DOI: 10.1111/tra.12531
|View full text |Cite
|
Sign up to set email alerts
|

Eps15R and clathrin regulate EphB2‐mediated cell repulsion

Abstract: Expression of Eph receptors and their ligands, the ephrins, have important functions in boundary formation and morphogenesis in both adult and embryonic tissue. The EphB receptors and ephrinB ligands are transmembrane proteins that are expressed in different cells and their interaction drives cell repulsion. For cell repulsion to occur, trans‐endocytosis of the inter‐cellular receptor‐ligand EphB‐ephrinB complex is required. The molecular mechanism underlying trans‐endocytosis is poorly defined. Here we show t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 63 publications
(187 reference statements)
1
18
0
Order By: Relevance
“…A large multi-domain protein, Eps15 binds physically to numerous other coat components, including AP-2 (Edeling et al, 2006; Benmerah et al, 1996; Traub et al, 1999; Schmid et al, 2006), Fcho1/2 (Henne et al, 2010; Reider et al, 2009; Uezu et al, 2011; Umasankar et al, 2012), Disabled-2 (Dab2) (Teckchandani et al, 2012), epsin 1 (Chen et al, 1998; McPherson et al, 1998), HIV-1 Rev-binding protein (Hrb) (Doria et al, 1999; Whitehead et al, 1999; Yamabhai et al, 1998), Numb (Santolini et al, 2000; Evergren et al, 2018), stonin 2 (Rumpf et al, 2008), and synaptojanin 1 (McPherson et al, 1998; Haffner et al, 1997), among other proteins including ubiquitin (Hofmann and Falquet, 2001). Because of this multiplicity of protein–protein contacts, residence of Eps15 at clathrin bud sites is not solely dependent on AP-2 (van Delft et al, 1997a).…”
Section: Introductionmentioning
confidence: 99%
“…A large multi-domain protein, Eps15 binds physically to numerous other coat components, including AP-2 (Edeling et al, 2006; Benmerah et al, 1996; Traub et al, 1999; Schmid et al, 2006), Fcho1/2 (Henne et al, 2010; Reider et al, 2009; Uezu et al, 2011; Umasankar et al, 2012), Disabled-2 (Dab2) (Teckchandani et al, 2012), epsin 1 (Chen et al, 1998; McPherson et al, 1998), HIV-1 Rev-binding protein (Hrb) (Doria et al, 1999; Whitehead et al, 1999; Yamabhai et al, 1998), Numb (Santolini et al, 2000; Evergren et al, 2018), stonin 2 (Rumpf et al, 2008), and synaptojanin 1 (McPherson et al, 1998; Haffner et al, 1997), among other proteins including ubiquitin (Hofmann and Falquet, 2001). Because of this multiplicity of protein–protein contacts, residence of Eps15 at clathrin bud sites is not solely dependent on AP-2 (van Delft et al, 1997a).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have suggested that SHIP2 can inhibit clathrin-mediated endocytosis (Nakatsu et al, 2010; Zhuang et al, 2007) by dephosphorylating phosphoinositides that promote endocytosis (Posor et al, 2015), whereas it promotes endophilin-mediated endocytosis (Boucrot et al, 2015). EphB-ephrinB interactions can lead to endocytosis of the complex in the forward and/or reverse direction, and this influences the strength of cell repulsion responses (Evergren et al, 2018; Gaitanos et al, 2016; Gong et al, 2019; Marston et al, 2003; Pitulescu and Adams, 2010; Zimmer et al, 2003). Furthermore, SHIP2 binds to EphA2 and inhibits its forward endocytosis (Zhuang et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…Constitutive KO: lethal prior to gastrulation [247]; conditional ubiquitous KO: mild proteinuria, mild increase in serum cholesterol, reduced tumor incidence [231,232,247,256,264] (see also [256] [195] Somatic mutations/gene fusion in AML and lung cancer [370,375] Eps15R (EPS15L1) Ubiqui-tin-UIM EphB2/ ephrinB [180], TfR [170] AP-2, CHC, Dynamin, Epsins, Intersectin, Numb, Stonin2, Synaptoja-nin…”
Section: Discussionmentioning
confidence: 99%
“…The C-terminal region comprises a proline-rich domain characterized by the presence of multiple DPF (aspartate-proline-phenylalanine) repeats, essential for the interaction with AP-2 [179] (Figure 2). In addition, Eps15R was shown to directly bind the Clathrin terminal domain [180]. In vitro studies, supported by structural data, first suggested that Eps15/Eps15R can form complexes with multiple endocytic proteins including AP-2, Dynamin, Intersectin1/2 and Stonin2, underlining their involvement in endocytosis [181,182].…”
Section: Ubiquitin Interacting Motif (Uim)-containing Adaptors: Eps15mentioning
confidence: 95%
See 1 more Smart Citation